Rural Farming Community Climate Change Acceptance: Impact of Science and Government Credibility - Evans, Chris; Storer, Christine; Wardell-Johnson, Angela (The International Journal of Sociology of Agriculture and Food, 2011)
Independent research of Western Australian rural people’s attitudes to climate change and influences on their attitudes offered a preliminary assessment of the WA rural sector’s understanding of climate change and insights into potential barriers to communication. Of the farmers surveyed (N=255) only a third (33%) reported to the researchers they agreed climate change was occurring and just 19% believed climate change was human induced. Over half (52%) were uncertain whether human-induced climate change was occurring and only 31% thought climate change represented a major threat to the future of their farm businesses. Results also showed that only 33% of all respondents (N =411) found climate change information easy to understand. In addition, results indicated that generally respondents had concerns with the credibility of science and low levels of trust in government, which contributed to their attitudes to climate change. These results suggested the barriers to climate change communication resided with the very structures that sought to communicate with rural people and were embedded in the comprehensibility, relevancy and saliency of climate change information. The results indicated that science and government may need to consider utilising alternative strategies to distribute climate change knowledge within the rural sector. The results suggest that a better approach to distributing climate change information would be to frame the information within the local socio-cultural, economic and biophysical environment of the people it was intended to influence.